Room temperature two terminal tunnel magnetoresistance in a lateral graphene transistor. Issue 47 (29th November 2021) - de Araujo, C. I. L.; Teixeira, H. A.; Toro, O. O.; Liao, C.; Benetti, L. C.; Borme, J.; Schafer, D.; Brandt, I.; Ferreira, R.; Alpuim, P.; Freitas, Paulo P.; Pasa, A. A.
Abstract : Spin transport is characterized in a lateral graphene transistor. Spin polarized electronic current is much more sensitive to scattering from defects than pure spin current. Here, the defects are controlled by external voltage and temperature variations. Abstract : We investigate the behavior of both pure spin and spin-polarized currents measured with four-probe non-local and two probe local configurations up to room temperature and under an external gate voltage in a lateral graphene transistor, produced using a standard large-scale microfabrication process. The high spin diffusion length of pristine graphene in the channel, measured both directly and by the Hanle effect, and the tuning of the relationship between the electrode resistance areas present in the device architecture allowed us to observe local tunnel magnetoresistance at room temperature, a new finding for this type of device. The results also indicate that while pure spin currents are less sensitive to temperature variations, spin-polarized current switching by an external voltage is more efficient, due to a combination of the Rashba effect and a change in carrier mobility by a Fermi level shift.